Nanotherapeutics as a localised drug delivery system for the treatment of GBM - Vasey, Catherine E (2021)
Glioblastoma multiforme (GBM) (recently classified by the World Health Organisation as glioblastoma isocitrate dehydrogenase wild-type or mutant), is the most common, malignant brain tumour in adults, mainly due to its rapid proliferation and ability to penetrate and diffusely infiltrate healthy brain parenchyma. Standard of care treatment consists of surgical debulking of the tumour, followed by an intense course of concomitant chemotherapy and radiotherapy. However, despite these multimodal treatment methods, and a greater understanding of disease biology, prognosis remains bleak with a median survival of 14 months from diagnosis.